2023
DOI: 10.1039/d3dt02999a
|View full text |Cite
|
Sign up to set email alerts
|

Electrophilic activation of molecular bromine mediated by I(iii)

Lachlan Sharp-Bucknall,
Tania,
Marcus Sceney
et al.

Abstract: In pursuit of a genuine Bromo-λ3-iodane, it has been found that the combination of Br2 and electron deficient λ3-iodanes can result in delivery of both bromine atoms from Br2 to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
(89 reference statements)
0
1
0
Order By: Relevance
“…For a method using I( iii ) in the rapid bromination of deactivated arenes we recently found that p -NO 2 -C 6 H 4 -IL 2 systems, where L is triflate or trifluoroacetate in concert with Br 2 enables the bromination of unreactive species including –CF 3 and – p -NO 2 substituted arenes ( Scheme 21 ). 96 The active intermediate is unknown at present but appears to arise from Lewis acidic activation of Br 2 by I(III) and then reoxidation of the HBr by-product by I(III), which is supported by the bromination of 2 equivalents of substrate per Br 2 and I(III) equivalent, achieving full consumption of the bromine. The advantage is brominations of deactivated arenes can be carried out rapidly at room temperature in organic solvent, whereas other methods for deactivated species require harsh media such as H 2 SO 4 solvent.…”
Section: Does Electrophilic Bromine As I–br Exist?mentioning
confidence: 99%
“…For a method using I( iii ) in the rapid bromination of deactivated arenes we recently found that p -NO 2 -C 6 H 4 -IL 2 systems, where L is triflate or trifluoroacetate in concert with Br 2 enables the bromination of unreactive species including –CF 3 and – p -NO 2 substituted arenes ( Scheme 21 ). 96 The active intermediate is unknown at present but appears to arise from Lewis acidic activation of Br 2 by I(III) and then reoxidation of the HBr by-product by I(III), which is supported by the bromination of 2 equivalents of substrate per Br 2 and I(III) equivalent, achieving full consumption of the bromine. The advantage is brominations of deactivated arenes can be carried out rapidly at room temperature in organic solvent, whereas other methods for deactivated species require harsh media such as H 2 SO 4 solvent.…”
Section: Does Electrophilic Bromine As I–br Exist?mentioning
confidence: 99%